Characterization of Local pH Changes in Brain Using Fast-Scan Cyclic Voltammetry with Carbon Microelectrodes - Takmakov, Pavel (2010)
Transient local pH changes in the brain are important markers of neural activity that can be used to follow metabolic processes that underlie the biological basis of behavior, learning and memory. There are few methods that can measure pH fluctuations with sufficient time resolution in freely moving animals. Previously, fast-scan cyclic voltammetry at carbon-fiber microelectrodes was used for the measurement of such pH transients. However, the origin of the potential dependent current in the cyclic voltammograms for pH changes recorded in vivo was unclear. The current work explored the nature of these peaks and established the origin for some of them. A peak relating to the capacitive nature of the pH CV was identified. Adsorption of electrochemically inert species, such as aromatic amines and calcium could suppress this peak, and is the origin for inconsistencies regarding in vivo and in vitro data. Also, we identified an extra peak in the in vivo pH CV relating to the presence of 3,4-dihydroxyacetic acid (DOPAC) in the brain extracellular fluid. To evaluate the in vivo performance of the carbon-fiber sensor, carbon dioxide inhalation by an anesthetized rat was used to induce brain acidosis induced by hypercapnia. Hypercapnia is demonstrated to be a useful tool to induce robust in vivo pH changes, allowing confirmation of the pH signal observed with FSCV.